FORMULASI DAN UJI STABILITAS BODY SCRUB EKSTRAK DAUN PEPAYA (Carica papaya L.) DENGAN VARIASI KONSENTRASI BIJI PEPAYA SEBAGAI EKSFOLIAT - Dewi Mutia Azizah; Dyera Forestryana; Nur Rahmiati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Body scrub is a topical formulation designed to remove dead skin cells, resulting in smoother and brighter skin. Papaya seeds (Carica papaya L.) have potential as a natural exfoliating agent, while papaya leaf extract is known to support skin regeneration. This study aimed to evaluate the physical characteristics and stability of a body scrub formulation containing papaya leaf extract with varying concentrations of papaya seeds as exfoliating agents. Papaya leaf extract was obtained using 70% ethanol as the solvent and formulated into an oil-in-water (O/W) cream with papaya seed variations of 5 g, 10 g, 15 g, 20 g, and 25 g. The evaluations included organoleptic properties, homogeneity, pH, viscosity, spreadability, adhesiveness, cream type, and physical stability using a six-cycle cycling test method. The results showed that all formulations exhibited good physical characteristics, with pH values ranging from 7.02 to 7.50, viscosity of 15,250–47,000 cPs, spreadability of 5.1–6.5 cm, and adhesiveness of 0.85–1.97 seconds. All formulations were homogeneous, physically stable, and classified as oil-in-water (O/W) creams. Formula F2 demonstrated the best physical characteristics among all tested formulations.